Cross-Sectional and Longitudinal Mental Health Status Prevailing among COVID-19 Patients in Mumbai, India - Arjun Gurmeet Singh; Hitesh Singhavi; Florida Sharin; Muffazal Lakdawala; Sharayu Mhatre; Jayita Deodhar; Pankaj Chaturvedi; Rajesh Dikshit (Wolters Kluwer Medknow Publications, 2022)
Introduction: The aim was to determine the prevalence and predictors of depression among less symptomatic COVID-19 patients. Methods: A questionnaire-based assessment was conducted among asymptomatic or mildly symptomatic COVID-19 patients when admitted in a COVID-19 facility (T1) and after 6 months (T2). Interviews were conducted using the Patient Health Questionnaire-9 instrument. Socio-demographic details and length of facility stay were recorded. Changes in scores between the two-time points T1 and T2 were compared. Factors predicting depression were determined using Chi-square and Mann-Whitney U test during facility stay, and those predicting worsening over time were obtained using multivariate regression models. Results: Among the 91.4% (n = 450) participants, prevalence of depression was 38.4% (95% confidence interval [CI] = 34.0-43.0) with a significant increase of 7.8-fold (95% CI = 4.8-12.8) in depression as the duration of stay increased beyond a median of 5 days. A significant association was observed between higher income and lower depression (odds ratios = 0.6, P = 0.03). 84% (n = 378) responded at the second timepoint assessment after a median of 6.62 months (T2). There was a significant difference observed between the 2.6% (n = 6) that worsened into depression at T2 and the 73.8% (n = 107) that improved out of depression at T2 (P ≤ 0.001). Age >45 years (P = 0.007), males (P = 0.011) and reinfection (P = 0.039) significantly led to worsening of depression. Conclusion: There is a need for actively detecting and managing depression in institutionally quarantined survivors, considering limiting such quarantine to no more than a week, and providing routine screening and care for depression beyond this period.